Has the mortality risk declined after the improvement of air quality in an ex-heavily polluted Chinese city-Lanzhou?. (March 2020) - Liu, Jiangtao; Ruan, Ye; Wu, Qi; Ma, Yueling; He, Xiaotao; Li, Lanyu; Li, Sheng; Niu, Jingping; Luo, Bin
Abstract: Lanzhou, an ex-heavily polluted city, was awarded "The Award for Today's Transformative Step" in 2015 World Climate Conference at Paris for its great efforts on air quality improvement since 2012. However, the health benefits from this improvement remain unclear. Therefore, we collected time-series data covering deaths, weather variables and air pollutants during the two periods (2004–2009, 2014–2017) and fitted single-pollutant models using the generalized additive models to evaluate the change of mortality risks associated with air pollutants in Lanzhou. Results showed that the annual average concentrations of respirable particulate matter (PM10 ) and sulfur dioxide (SO2 ) dropped by 19.28% and 66.29%, while the nitrogen dioxide (NO2 ) increased by 16.61% in 2014–2017 compared to 2004–2009. During the period 2004–2009, we found a 10-μg/m 3 increase in PM10 (lag 2), SO2 (lag 0–5) and NO2 (lag 0–5) were associated with mortality increments of 0.12% (95% CI: 0.01, 0.22), 0.86% (95% CI: 0.42, 1.31) and 1.29% (95% CI: 0.70, 1.90), respectively. During the period 2014–2017, the association between PM10 and daily deaths was not significant, but we observed a 10-μg/m 3 increase in SO2 (lag 0–5) and NO2 (lag 4) were related to mortality increments of 4.23% (95% CI: 1.82, 6.70) and 0.85% (95% CI: 0.19, 1.52), respectively. From 2004–2009 to 2014–2017, we observed markedly decline of mortality risk due to PM10, but not SO2 or NO2 . In conclusion, the mortality risk of PM10 in Lanzhou has declined obviously after the substantially improved air quality due to the enforcement of air pollution controlling policies. Highlights: The mortality risks due to air pollutants were assessed before and after air pollution controlling in Lanzhou. The air pollution of Lanzhou improved substantially from 2004 to 2017. The mortality risks due to PM10 decreased after air pollution reduction. The death risks of air pollutants were higher in the heating period of Lanzhou.